PENGARUH TINGKAT EKSPOR DAN PENGANGGURAN TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA PADA TAHUN 2019-2023 - Maya Sentia Enjelika Tampubolon; Cornelia Aginta Br Sembiring; Melisa Patrisia Manurung (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2024)
This research aims to analyze the influence of export levels and unemployment on economic growth in Indonesia in the 2019-2023 period. Using secondary data from the Central Statistics Agency and Bank Indonesia as well as multiple linear regression analysis methods, the research results show that exports have a positive but not significant impact on economic growth, with a calculated t value of 2.328 and a significance value of 0.145. On the other hand, unemployment has a negative and significant effect on economic growth, with a calculated t value of 5.096 and a significance value of 0.036. The simultaneous test shows that these two variables together have a significant effect on economic growth, with a calculated F value of 20.871. This research concludes that although exports do not have a significant effect, reducing unemployment must be the main focus to support sustainable economic development in Indonesia.